Impact of Environmental Pollution (Dumpsite and Vehicle Exhaust) On the Green Vegetable (Amaranthus Hybridus), Jute-Ewedu (Corchorus Olitorius) and Spinach (Amaranthus Oleracea) Planted in Alimosho Local Government Area, Lagos State, Nigeria - Gidigbi, Joshua A; Abubakar, Abdulrasaq B; Aisuedion, Martins E; Barnabas, Henry L (International Journal of Chemistry and Materials Research, 2022)
This study assessed the effect of the dumpsite and vehicle exhaust on green leaf vegetable (Amaranthus hybridus), Jute-ewedu (Corchorus olitorius), and spinach (Amaranthus oleracea) by examining the heavy metal distribution in three vegetables from Ipaja farm (farm near a dumpsite), and Ikola farm (farm close to the tarred road) and compared with the concentration of heavy metals from Shasha farm (a secluded farm) and World Health Organisation/ Food and Agriculture Organisation (WHO/FAO) standard. The leaves of these vegetables were air-dried, digested, and analysed for the presence of Arsenic (As), Magnesium (Mn), Copper (Cu), Zinc (Zn), Lead (Pb) and Cadmium (Cd) using Atomic Absorption Spectrophotometry. The heavy metals values at Shasha farm were within the permissible range set by WHO/FAO. However, at the Ipaja farm, Lead and Cadmium were beyond the WHO/FAO permissive range in green-leaf (2.311±0.003mg/kg, 0.201±0.013 mg/kg), while only Lead in Jute-ewedu (2.011±0.003 mg/kg) and Spinach (2.011±0.003mg/kg). At the Ikola farm, Arsenic, Lead and Cadmium were beyond the WHO/FAO acceptable value in green vegetable (0.329±0.012 mg/kg, 4.122±0.007 mg/kg, 2.941±0.0011 mg/kg), while only Lead and Cadmium in Jute-ewedu (3.241±0.007mg/kg, 2.391±0.005 mg/kg), and Spinach (3.69±0.015mg/kg, 2.32±0.004 mg/kg). The increase in the metal concentration from the Ipaja farm suggests the feasibility of metal mobility from the dumpsite to the nearer farm. Also, vehicular exhaustion may contribute to the increase of Cadmium and Lead present in the vegetables planted along the tarred road. Government should dissuade citizens from creating improper dumpsites and ensure vegetable farms are cited away from the main road.